If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 5) + 3 = 7 Reorder the terms: 2(5 + x) + 3 = 7 (5 * 2 + x * 2) + 3 = 7 (10 + 2x) + 3 = 7 Reorder the terms: 10 + 3 + 2x = 7 Combine like terms: 10 + 3 = 13 13 + 2x = 7 Solving 13 + 2x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 2x = 7 + -13 Combine like terms: 13 + -13 = 0 0 + 2x = 7 + -13 2x = 7 + -13 Combine like terms: 7 + -13 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 2x+4x-4=20 | | 3x-24-5x=7x+24 | | 3x-24-5x=7x+24 | | 2X^2=X^2-12 | | 30-20+2x=10 | | 81-5x=22x+18 | | 0=3x^2+4x+5 | | 5-7x=73-35x | | 0=x^2-7x+11 | | x+30=40 | | -(-8x)=(-78) | | x=420000+3x+1+6x+1+9x+1 | | X^2+15=7 | | 8x+8=47 | | 2x^2+8x-64=0 | | 14=-z+3 | | 0=x^2-7x-8 | | 8x+8=40 | | .05x+.10(140-x)=11.15 | | 18=-z+4 | | 15x^2+15=34x | | 4x+3z=3 | | 0=x^2+2x+9 | | 0=2x^2+4x-3 | | 4x(x+1)=75+x(x+4) | | 21.5=a-1.5 | | -(-9x)=(-37) | | (x-1)(x-1)=4 | | y=x^2-5x-14 | | -16x^2+24x+5=0 | | 4x(x+1)=75+x(x+7) | | 5n^2+20n+15=0 |